Efeitos da fotobiomodulação com diodos emissores de luz (LEDs), vermelhos e infravermelhos, sobre aspectos clínicos em pacientes com disfunção temporomandibular: estudo clínico, randomizado, controlado e duplo-cego - Sousa, Dowglas Fernando Magalhães de (2020)
Temporomandibular disorder - TMD is a term referring to abnormalities that occur on the temporomandibular joints - ATMs and/or the muscles of mastication. Photobiomodulation by means of the light emitting diode - LED comes as another therapeutic option in the treatment of patients with TMD, promoting pain monitoring and improving the range of mandibular movement. The study aimed to evaluate the effects of photobiomodulation with simultaneous use of LEDs, red (660 nm) and infrared (850 nm), on pain, the range of mandibular movement in individuals with TMD. A controlled, randomized, double-blind clinical trial was carried out on 18 women diagnosed with TMD, assessed using: Research Diagnostic Criteria for Temporomandibular Disorder questionnaire, visual analog scale, and mandibular range of motion. The research volunteers were evaluated and remained for two weeks without any intervention, then randomly allocated to one of two groups: LED group (photobiomodulation three times a week with an interval between sessions, for 2 weeks, totaling 6 non-consecutive sessions treatment ) and Control Group (equipment disconnected as placebo). We used a device with 18 red LEDs - 660 nm and 18 infrared LEDs - 850 nm, radiant exposure of 5.35 J / cm2, total power of 126 mW, irradiation of 4.45 mW / cm2 per point with exposure time of 1200 seconds, resulting in an energy of 75.6 J per point, and total radiated energy of 907.2 J per participant, in the regions of the ATMs, and of the masseter and temporal muscles. From an initial sample of 78 volunteers, 18 women, with a mean age of 23.61 (± 3.68) years, were randomized between January 2019 and December 2019. For the pain outcome, there was a statistically significant difference in the comparison between LED treatment and the control group at the end of the treatment (p = 0.0013), as well as in the comparison between the beginning and the end of LED treatment (p = 0.0002). The outcome range of mandibular movement was evaluated in the conditions of opening without assistance and without pain, maximum opening without assistance, maximum opening with assistance, right lateral excursion, left lateral excursion and protrusion. There was no statistically significant difference in the comparison between treatment with LED and the control at the end of treatment for any of the conditions (p> 0.05), as well as in the comparison between the beginning and end of treatment with LED (p> 0.05) ). No studies have been found, so far, with the use of photobiomodulation using a device with 18 red LEDs (660nm) and 18 infrared LEDs (850nm) combined in a plate. This combination can help to reduce pain in individuals with temporomandibular disorders, however there was no improvement in the range of motion of mandibles in these individuals using the same treatment. We conclude that photobiomodulation using both red and infrared LEDs demonstrated a positive effect in reducing pain in individuals with temporomandibular disorder after six non-consecutive sessions.